Effect of cutting parameters on surface roughness in turning of annealed AISI-1020 steel - Zurita Hurtado, Omar José; Di Graci Tiralongo, Verónica Carmen; Capace Aguirre, María Cristina (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 111-118).